PENERAPAN TEKNOLOGI TEPAT GUNA PADA PENGOLAHAN SARI DAN ES PUTER TEMPE DI KAMPUNG TEMPE DESA PAREREJO KECAMATAN PURWODADI KABUPATEN PASURUSAN - Anugerah Dany Priyanto; Sri Djajati; Jariyah (Universitas Nahdlatul Ulama Sidoarjo, 2019)
Parerejo Village, Purwodadi Subdistrict, Pasuruan Regency, which is famous for its tempeh village because most of patriarch work as tempeh craftsmen. The majority of tempe craftsmen sell their product only fresh tempeh and the minority processing the tempeh into chips and nuggets. This has an impact on the disposal of unsold tempeh due to its short shelf life. The program has the targets community were the wives of tempeh craftsmen with the aim of helping their husbands. This program applies appropriate technology from the science of food technology to processing fresh tempeh. Fresh tempeh products were processed into two types of diversification, namely tempeh juice and es puter. The training was carried out using the verbal language of the local community with the aim were easily delivered of knowledge and can be accepted by the community. Socialization and training can also be carried out well that can be known by looking at the community's response with enthusiasm and the sustainability of the program which will be carried out continuously in a coordinated manner by the chairman of the tempeh craftsmen community. The results of this program can be concluded that community service to tempeh craftsmen is very useful and the community hopes that the product can continue until it is ready for production and commercial in the market.